Odpowiedzi

  • Użytkownik Zadane
2013-07-14T14:15:10+02:00

 

2(x-y)(x+y)-3(x+2y)^2+(x-y)^2=

 

2(x^2-y^2)-3(x^2+4xy+4y^2)+x^2-2xy+y^2=

 

2x^2-2y^2-3x^2-12xy-12y^2+x^2-2xy+y^2=

 

- 14xy - 13y^2

 

-14\cdot \sqrt{2}\cdot \frac{ \sqrt{2} }{2}-13\cdot ( \frac{ \sqrt{2} }{2} )^2 =-14-13\cdot \frac{1}{2}=-14-6,5=-20,5

================

( \sqrt{2} x - 1)( \sqrt{2} x +1)-( \sqrt{2} x -1)^2+(x - \sqrt{2} )^2=

 

2x^2-1-(2x^2-2 \sqrt{2}x+1)+x^2-2 \sqrt{2}x+2=

 

2x^2-1-2x^2+2 \sqrt{2}x-1+x^2-2 \sqrt{2}x+2=

 

x^2

 

(- \sqrt{3})^2=3